Partnerships as signposts? The role of spatial mobility in gendered earnings benefits of graduates - Detemple, Jonas [Verfasser] (My University, 2025)
„This study analyzes the gender-specific impact of spatial mobility on earnings after graduation from higher education, extending previous research on graduates’ mobility benefits, which has largely ignored gender-specific mechanisms. Based on household economic and gender role considerations, this study argues that partnerships are associated with solidifying gender differences in mobility-related earnings benefits. The study uses data from the German National Educational Panel Study (NEPS), Starting Cohort First-Year Students (SC5), and applies entropy balancing weights to account for the self-selection of mobile graduates. General linear models show a weak correlation between overal graduate mobility and higher earnings and that gender differences are rather small and depend on the type of mobility. However, looking at the role of partnerships, female graduates benefit significantly less from short-distance mobility when cohabiting with a partner than their non-cohabiting counterparts, while cohabiting male graduates benefit significantly more from long-distance mobility. The findings contribute to the literature by highlighting the crucial role of partnerships in the gendered mobility benefits of graduates.“ (author’s abstract; BIBB-Doku)
Keywords: S 1.4 Hochschulbildung; G 1.3.3.3 Mobilität; 370; 330; 300; Hochschulbildung; Akademiker; Einkommen; Einkommensunterschied; Einflussfaktor; Mobilität; Regionale Mobilität; Geschlechtsspezifische Faktoren; Partnerschaft